Chasing the smokestack: Strategic policymaking with multiple instruments - Per G. Fredriksson; John A. List; Daniel L. Millimet (Fondazione Eni Enrico Mattei (FEEM), 2002)
Recent studies suggest a considerable amount of horizontal strategic interaction amongst governments exists. The empirical approach in these studies typically relies on estimating reaction functions in a uni-dimensional policy framework, where a nonzero slope estimate suggests strategic interactions exist. While this framework may be useful within certain contexts, it is potentially too restrictive; for example, in models of resource competition, locales may use multiple instruments to attract agents, leading to strategic interaction across policy instruments. In this study, we develop a theoretic construct that includes yardstick competition in a world of multi-dimensional policies to show that while a zero-sloped reaction function may exist for any particular policy, this does not necessarily imply the absence of strategic interactions. We empirically examine the implications of the model using US state-level panel data over the period 1977-1994. Empirical results suggest important cross-policy strategic interactions exist, lending support in favor of the multi-dimensional framework
Keywords: C33; H7; R1; R3; Q28; 330; Political economy; resource competition; strategic policymaking; yardstick competition; Institutioneller Wettbewerb; Neue politische Ökonomie; Umweltpolitik; Infrastrukturpolitik; Steuerpolitik; Theorie; USA; Landespolitik